The effects of Quaternary glaciations in Patagonia as evidenced by chloroplast DNA phylogeography of Southern beech Nothofagus obliqua - Azpilicueta, Maria Marta (2009)
Climatic oscillations during the Quaternary strongly affected the distribution of warm-temperate tree species, which experienced local restrictions into ice-free areas and posterior expansions. To evaluate the impact of these range movements on the genetic structure of populations, we performed a phylogeographical analysis of the species Nothofagus obliqua with chloroplast DNA markers. A total of 27 populations covering the whole natural distribution range were analyzed using polymerase chain reaction-restriction fragment length polymorphism. Diversity (hT, hS), allelic richness (rg), and differentiation among populations for unordered (GST) and ordered alleles (NST) were calculated. The relationships among haplotypes were evaluated by the construction of a minimum spanning network. The spatial distribution of the genetic variation was analyzed through a Mantel test and with a nested analysis of molecular variance to differentiate between geographic regions. The screening of 11 non-coding regions allowed the identification of 14 haplotypes. A high genetic differentiation was detected (NST=0.875 and GST= 0.824) with the existence of phylogeographic structure (p< 0.05). The distribution of the genetic variation was partially explained by the topography of the region when the populations were divided longitudinally into Coastal Mountains, Central Valley, and Andes Mountains (RT=0.093, p=0.001). In agreement with pollen records, our results support the hypothesis of Coastal refuges since the region harbors high diversity together with older and private haplotypes. Long-lasting persistence of some Coastal populations without contribution to recolonization is proposed. Additional refuges are also postulated along the Andes and Longitudinal Valley. Survival in multiple glacial refuges is discussed together with the possible migratory routes.